2009
DOI: 10.1074/jbc.m109.020107
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Glutathione Conjugates of Fatty Acid Derivatives by Plant Glutathione Transferases

Abstract: Proteomic studies with Arabidopsis thaliana have revealed that the plant-specific Tau (U) class glutathione transferases (GSTs) are selectively retained by S-hexylglutathione affinity supports. Overexpression of members of the Arabidopsis GST superfamily in Escherichia coli showed that 25 of the complement of 28 GSTUs caused the aberrant accumulation of acylated glutathione thioesters in vivo, a perturbation that was not observed with other GST classes. Each GSTU caused a specific group of fatty acyl derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 35 publications
2
69
0
Order By: Relevance
“…Seven glutathione S-transferase (GST) genes are present in two clusters (26 and 30) overrepresented for this term and are upregulated around 14 HAI. All seven genes (GSTU3, GSTU7, GSTU8, GSTU10, GSTU19, GSTU24, and GSTU25) are members of the Tau family of GSTs, which are plant specific and can bind glutathione conjugated fatty acid derivatives (Dixon and Edwards, 2009). Although the precise function of these GSTs is not known, GSTU19 and GSTU25 both have high conjugating activity toward the xenobiotic 1-chloro-2,4-dinitrobenzene, used as an indicator of detoxifying activity.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven glutathione S-transferase (GST) genes are present in two clusters (26 and 30) overrepresented for this term and are upregulated around 14 HAI. All seven genes (GSTU3, GSTU7, GSTU8, GSTU10, GSTU19, GSTU24, and GSTU25) are members of the Tau family of GSTs, which are plant specific and can bind glutathione conjugated fatty acid derivatives (Dixon and Edwards, 2009). Although the precise function of these GSTs is not known, GSTU19 and GSTU25 both have high conjugating activity toward the xenobiotic 1-chloro-2,4-dinitrobenzene, used as an indicator of detoxifying activity.…”
Section: Metabolismmentioning
confidence: 99%
“…Although the precise function of these GSTs is not known, GSTU19 and GSTU25 both have high conjugating activity toward the xenobiotic 1-chloro-2,4-dinitrobenzene, used as an indicator of detoxifying activity. However, GSTU19 can conjugate glutathione onto oxylipins, suggesting that it may play a role in modulating jasmonate signaling (Dixon and Edwards, 2009). In addition to toxin detoxification, cells are able to prevent toxin accumulation through sequestration in the vacuole or active transport out of cells.…”
Section: Metabolismmentioning
confidence: 99%
“…The excess light-induced ROS defense mechanism is also linked to JA signaling through transcriptional regulation (43). Previous research revealed that overexpression of members of the Arabidopsis GST superfamily in Escherichia coli resulted in 25 of the 28 GST tau (U) proteins (GSTUs) causing an aberrant accumulation of acylated GSH thioesters in vivo, a perturbation that was not observed with other GST classes (47). In particular, the study demonstrated that GSTU members catalyzed the S-glutathionylation of 12-oxo-phytodienoic acid (OPDA), an early biosynthetic precursor of JA (28,47).…”
Section: The Conserved Residues Compose Three Motifs: Motif I (S/t-mentioning
confidence: 99%
“…Previous research revealed that overexpression of members of the Arabidopsis GST superfamily in Escherichia coli resulted in 25 of the 28 GST tau (U) proteins (GSTUs) causing an aberrant accumulation of acylated GSH thioesters in vivo, a perturbation that was not observed with other GST classes (47). In particular, the study demonstrated that GSTU members catalyzed the S-glutathionylation of 12-oxo-phytodienoic acid (OPDA), an early biosynthetic precursor of JA (28,47). Further research is required to determine whether FIP1 plays a role in other regulatory mechanisms in jasmonic acid signaling, such as preventing epimerization of the active (+)-7-iso-jasmonoyl-L-isoleucine attaching to the inactive (−)-jasmonoyl-L-isoleucine.…”
Section: The Conserved Residues Compose Three Motifs: Motif I (S/t-mentioning
confidence: 99%
“…GST isoenzymes are encoded by a gene family divided into different classes based on sequence similarities and biochemical function (Edwards et al, 2000;Wagner et al, 2002). Most GSTs belong to the phi and theta classes and participate in detoxification reactions by catalyzing the conjugate formation between electrophilic compounds and the antioxidant glutathione (GSH) (Wagner et al, 2002;Dixon and Edwards, 2009a;Dixon et al, 2011). However, certain tau class GSTs possess a glutathione-peroxidase activity and are able to catalyze the breakdown of H 2 O 2 and lipid hydroperoxides (Bartling et al, 1993;Dixon et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%